The emergence of the church : context, growth, leadership & worship - Patzia, Arthur G. (Downers Grove, Ill. : InterVarsity Press, 2001)
"The Emergence of the Church explores the story, weighs the issues and traces the contours of the early church's expansion and growth, life and practices, leadership and worship. Here is a panoramic introduction to the church as it was in the first century and a foundation for considering how it should be in the twenty-first century."--BOOK JACKET.
The geographical, religious & cultural background to the early church -- Jesus & the church -- The geographical expansion, numerical growth & diversity of the early church -- The emergence of ministry, leadership & church order in the early church -- Worship in the early church -- Concluding remarks.
Includes bibliographical references (p. [252]-260) and indexes.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Vroege kerk; Ontstaansgeschiedenis